Giúp mình với, giải ra nha! \(\frac{\sqrt{6-2\sqrt{5}}}{\sqrt{5}-1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\sqrt{4\left(1-x\right)^2}-12=0\)
\(\sqrt{4\left(1-x\right)^2}=0+12\)
\(\sqrt{4\left(1-x\right)^2}=12\)
\(\left[\sqrt{4\left(1-x\right)^2}\right]^2=12^2\)
\(4-8x+4x^2=144\)
\(\Rightarrow\orbr{\begin{cases}x=7\\x=-5\end{cases}}\)
b) \(\sqrt{4x^2-12x+9}=5\)
\(\left(\sqrt{4x^2-12x+9}\right)^2=5^2\)
\(4x^2-12x+9=25\)
\(\Rightarrow\orbr{\begin{cases}x=4\\x=-1\end{cases}}\)
a)= \(\frac{\sqrt{2}-1}{2-1}+\frac{\sqrt{3}-\sqrt{2}}{3-2}+...+\frac{\sqrt{100}-\sqrt{99}}{100-99}\)
=\(\sqrt{2}-1+\sqrt{3}-\sqrt{2}+...+\sqrt{100}-\sqrt{99}\)
= \(-1+\sqrt{100}\)
= -1 +10
=9
b)Ta có\(\left(\sqrt{n+1}-\sqrt{n}\right)\cdot\left(\sqrt{n+1}+\sqrt{n}\right)\)=n+1-n=1 (1)
Lại có:\(\frac{1}{\sqrt{n+1}+1}\cdot\left(\sqrt{n+1}+1\right)=1\)(2)
Từ (1) và (2)=>\(\left(\sqrt{n+1}-1\right)=\frac{1}{\sqrt{n+1}+1}\)
\(E=\frac{2}{\sqrt{3}}+\frac{\sqrt{2}}{3}+\frac{2}{\sqrt{3}}.\left(\frac{5}{12}-\frac{1}{\sqrt{6}}\right)\)
\(E=\frac{2}{\sqrt{3}}+\frac{\sqrt{2}}{3}+\frac{5\sqrt{6}-12}{18\sqrt{2}}\)
\(E=\frac{36\sqrt{2}}{18\sqrt{6}}+\frac{12\sqrt{3}}{18\sqrt{6}}+\frac{\left(5\sqrt{6}-12\right).\sqrt{3}}{18\sqrt{3}}\)
\(E=\frac{36\sqrt{2}+12\sqrt{3}+\left(5\sqrt{6}-12\right).\sqrt{3}}{18\sqrt{6}}\)
\(E=\frac{51\sqrt{2}}{18\sqrt{6}}\)
\(E=\frac{17\sqrt{2}}{6\sqrt{6}}\)
\(E=\frac{17\sqrt{2}}{2.3\sqrt{2}.\sqrt{3}}\)
\(E=\frac{17}{\sqrt{2}.3\sqrt{2}.\sqrt{3}}\)
\(E=\frac{17}{6\sqrt{3}}\)
\(E=\frac{17\sqrt{3}}{18}\)
Ta có: \(\frac{2}{\sqrt{3}}+\frac{\sqrt{2}}{3}+\frac{2}{\sqrt{3}}\sqrt{\frac{5}{12}-\frac{1}{\sqrt{6}}}\)
\(=\frac{2\sqrt{3}}{3}+\frac{\sqrt{2}}{3}+\frac{2\sqrt{3}}{3}\sqrt{\frac{5}{12}-\frac{1}{\sqrt{6}}}\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}.\sqrt{12}.\sqrt{\frac{1}{12}-\frac{1}{\sqrt{6}}}\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}.\sqrt{12\left(\frac{5}{12}-\frac{1}{\sqrt{6}}\right)}\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}\sqrt{5-2\sqrt{6}}\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}.\sqrt{\left(\sqrt{3}-\sqrt{2}\right)^2}\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}\left|\sqrt{3}-\sqrt{2}\right|\)
\(=\frac{2\sqrt{3}+\sqrt{2}}{3}+\frac{1}{3}\left(\sqrt{3}-\sqrt{2}\right)\)(vì \(\sqrt{3}-\sqrt{2}>0\))
\(=\frac{2\sqrt{3}+\sqrt{2}+\sqrt{3}-\sqrt{2}}{3}=\sqrt{3}\)
\(\sqrt{\left(3-\sqrt{5}\right)^2}+\sqrt{6-2\sqrt{5}}\)
\(=3-\sqrt{5}+\sqrt{\left(\sqrt{5}-1\right)^2}\)
\(=3-\sqrt{5}+\sqrt{5}-1=2\)
\(\sqrt{9+4\sqrt{5}}=\sqrt{\left(\sqrt{5}+2\right)^2}-\sqrt{5}\)
\(=\sqrt{5}+2-\sqrt{5}=2\)
Chúc học tốt!!!!!!!!!!!!!